A Study of Reading Strategies Used by English Study Program Students - Rahmawati, Uci; Eliwarti, Eliwarti; Supriusman, Supriusman; Supriusman, Supriusman (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to explore the types and frequency of reading strategies used by fourth-semester students in Riau University’s English Department. This study employed a descriptive-quantitative design, using the Survey of Reading Strategies (SORS) by Mokhtari and Sheorey (2002). Data was collected from 38 students through an online questionnaire, with the results showing that the Problem Solving Strategy was the most frequently used (M = 4.04), followed by the Global Reading Strategy (M = 3.81) and the Supportive Reading Strategy (M = 3.70). These findings suggest that students rely on problem-solving strategies to overcome comprehension challenges, while global strategies help them manage the reading process. Supportive strategies, while still useful, are used more selectively. The study concludes that students actively use a combination of strategies, reflecting a positive level of metacognitive awareness. The study also recommends that English lecturers provide more explicit training on global strategies and supporting strategies to improve students’ reading ability.